Audit Quality and ESG Signaling: A Mediation Analysis from Selected Emerging Markets on Firm Value Addition - Siddiqui, Ozair; Raheman, Abdul (Indonesian Journal of Sustainability Accounting and Management, 2026)
This study is among the first to investigate whether ESG (Environmental, Social, and Governance) factors mediate the relationship between audit quality and value addition of non-financial firms in the selected emerging markets, using the theoretical lens of signaling theory. More specifically, the study focuses on BRICST (Brazil, Russia, India, China, South Africa, and Turkey) economies and uses Seemingly Unrelated Regression (SUR) system and bootstrapping to perform the mediation analysis on unbalanced panel data. The results show evidence that ESG does mediate the relationship between audit quality and value addition; however, contrary to the notions of stakeholder theory, the indirect effect is negative. Similarly, the direct impact of audit quality on value addition also remains negative. The study contributes theoretically by refining signaling theory through the lens of institutional and contextual factors. It demonstrates that both audit quality and ESG scores act as signals for stakeholders. Practically, the findings highlight the need to integrate ESG practices into the overall firm strategy, showing that ESG disclosures in emerging markets remain symbolic without strategic integration. The findings also highlight growing stakeholder expectations beyond assurance of financial information, covering the credibility of ESG disclosures as well.